Dinamika Psikologis Anak Usia Dasar : Keterkaitan Motivasi, Disiplin, dan Lingkungan Fisik Kelas di MI - Didit Darmawan; Laylatul Mubarok (Universitas Muhammadiyah Surabaya, 2026)
This study aims to analyze conceptually the relationship between intrinsic motivation and discipline in shaping learning independence of elementary school age children in Madrasah Ibtidaiyah Negeri, as well as examining the arrangement of inspirational physical classroom environment to stimulate motivation and behavioral regularity. This qualitative literature study traces various scientific sources discussing motivational psychology, discipline formation, and the influence of physical environment on children's learning behavior. Data were analyzed using content analysis method with reference to the thoughts of educational and psychological experts. The findings show that intrinsic motivation rooted in children's natural curiosity becomes the strongest and most durable driving energy for learning. When psychological needs for autonomy, competence, and relatedness are fulfilled in madrasah, children develop a love of learning that encourages perseverance. This perseverance gradually forms regular habits which are the core of self discipline. On the other hand, physical classroom environment including lighting, wall colors, seating arrangements, display of work, reading corners, plants, cleanliness, and acoustics collectively form an ecosystem that supports learning motivation and teaches regularity values nonverbally. The synergy between psychological need fulfillment and inspirational physical environment creates optimal conditions for the development of learning independence in MIN students. This study implies the need for a paradigm shift in discipline development towards a humanistic approach and serious attention to classroom ecological arrangement.